Ethnoscience of the Blue-eyed Cuscus as a Learning Resource for Island Science in Elementary Schools - Wawan Suprianto Nadra; Rasmi Hi. Panu; Eko Purnomo (FKIP Universitas Khairun, 2026)
This study aims to explore the local knowledge of communities surrounding Lake Tolire regarding the blue-eyed cuscus (Phalanger matabiru) and to analyze its potential as a contextual learning resource for island-based science education in elementary schools. The research employed a qualitative exploratory design using an ethnoscience approach. Data were collected through field observations, semi-structured interviews with local community members and elementary school teachers, and documentation. The data were analyzed through stages of data reduction, data display, and conclusion drawing to identify scientific concepts embedded in community knowledge. The findings reveal that local communities possess ecological knowledge related to the behavior, habitat, and feeding patterns of the blue-eyed cuscus, including its nocturnal activity, arboreal lifestyle, and consumption of fruits and leaves within forest ecosystems. This knowledge reflects traditional ecological understanding developed through long-term interactions between humans and their natural environment. Furthermore, the identified local knowledge can be transformed into scientific concepts relevant to the elementary Integrated Science and Social Studies (IPAS) curriculum, such as living organism adaptation, habitat relationships, food chains, and forest ecosystems.